Causal Link between Financial Globalisation Uncertainty, Economic Growth, Environmental Degradation and Energy Consumption in ASEAN+3 Countries - Ismail, Suraya; Roslan, Farah; Endut, Wan Anisah; Ismail, Noris Fatilla; Atiku, Abubakar Mohammed; Ahmad, Ali Umar (International Journal of Energy Economics and Policy, 2024)
This paper aims to examine the causal linkage of financial globalisation uncertainty, Environmental Degradation, economic growth and energy consumption for ASEAN+3 countries using second-generation approach for the period between 1970–2019. The results of second-generation unit root test revealed that economic growth and financial globalisation uncertainty were stationary at level, while energy consumption and environmental degradation were stationary at first difference. In addition, the Larson cointegration test showed that long-run cointegration exists between the variables. Similarly, we found that economic growth and environmental degradation have significant positive influence on energy consumption. However, financial globalisation uncertainty has insignificant influence on energy consumption. The results of causal relationship indicated a bidirectional causal relationship between financial globalisation uncertainty and energy consumption; environmental degradation and energy consumption; and economic growth and energy consumption.